Short-Term Measurements of Household Electricity Demand During Hot Weather in Kuala Lumpur - Nassir Ranjbar; Sheikh Ahmad Zaki; Nelidya Md Yusoff; Fitri Yakub; Aya Hagishima (Institute of Advanced Engineering and Science, 2017)
The aim of this study was to conduct short-term measurements on household electricity demand under hot weather conditions in a residential area in Kuala Lumpur. The measurements included total and air conditioner (AC) electricity consumption of 10 households in an apartment building as well as outdoor air temperatures, which were collected from March to May 2016. Results indicated that the average AC electricity consumption contributed to a major portion of total household electricity consumption, which ranged from 19.4 to 52.3% during the measurement period. Additionally, 1-minute interval time series data indicated household energy consumption more accurately than 30- or 60-minute interval.